The Relationship Between Psychological Well-Being and Organizational Commitment of Market Employees - Adoe, Erikson; Wijaya, R. Pasifikus Christa; Pello, Shela Christine (Journal of Health and Behavioral Science, 2025)
Organizational commitment is a measure of an employee's willingness to stick with a company in the future. An employee's organizational commitment can be influenced by various factors: the work environment, the psychological well-being of employees, and the company's existing regulations. The purpose of this study is to find out whether there is a relationship between psychological well-being and organizational commitment in Transmart Kupang employees. This research employs a quantitative technique with correlational methods. The population of this study consist of all Transmart Kupang employees, totaling 80 people. Data was obtained using a psychological well-being scale and an organizational commitment scale. The data was analyzed using a Pearson correlation test with the help of the SPSS application. The results of the person correlation test showed a sig. 0.000 < 0.05, which indicates that there is a relationship between psychological well-being and organizational commitment in Transmart Kupang employees.